2019
DOI: 10.1186/s41936-019-0117-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cassava peel meal, methionine, and multi-enzyme supplementation in rabbits’ nutrition: effect on growth, digestibility, and carcass traits

Abstract: Background: This study was carried out to assess the performance indices, nutrient digestibility, and carcass trait of weaner rabbits fed diets containing cassava peel meal (CPM) supplemented with methionine (MET) and multi-enzyme (ENZ). Two hundred and forty 5-week-old growing rabbits were randomly allotted to 8 dietary treatments (10 replicates/treatment) in a factorial arrangement (2 × 2 × 2) of 2 CPM inclusion levels (0 and 35%), 2 MET levels (0.56 and 0.83%), and 2 ENZ levels (0 and 0.05%). Results: The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The carcass weights obtained in this study are better than those reported by Ojebiyi et al (2013) who obtained lower weight at slaughter despite an older age (105 days). Carcass yields in the present study are similar to those reported with rabbits of hybrid breeds in W est Africa (Oloruntola et al, 2019).…”
Section: Characteristics Of the Carcasssupporting
confidence: 89%
“…The carcass weights obtained in this study are better than those reported by Ojebiyi et al (2013) who obtained lower weight at slaughter despite an older age (105 days). Carcass yields in the present study are similar to those reported with rabbits of hybrid breeds in W est Africa (Oloruntola et al, 2019).…”
Section: Characteristics Of the Carcasssupporting
confidence: 89%
“…These results agree with others previously obtained, where lysine, methionine or threonine supplementation did not affect the digestibility of DM, CP, and GE [ 32 , 33 , 34 ]. However, recent studies have observed that dietary supplementation with methionine from 2.4 to 4.9 g/kg [ 35 ] or from 5.6 to 8.3 g/kg [ 36 ] could increase the CTTAD of DM, CP and GE in growing rabbits. In any case, ref.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Abo El-Maaty et al ( 2019) illustrated that replacing of 15% of dietary yellow corn by wheat bran supplemented with 0.05% enzymes (xylanase, β-glucanase, α-amylase, protease, and phytase) enhanced nutrients' digestibility of DM, CP, and EE in growing rabbits. Similarly, Oloruntola et al (2019) observed that dietary supplementation of 0.05% multienzyme (cellulase, α-amylase, β-glucanase, phytase, protease, lipase, and xylanase) alleviated the negative effects of inclusion of 35% cassava peels in the diets and enhanced growth performance and carcass characteristics .…”
Section: Exogenous Enzymesmentioning
confidence: 89%